Consensus guidelines for the definition, detection and interpretation of immunogenic cell death. Issue 1 (9th March 2020) - Galluzzi, Lorenzo; Vitale, Ilio; Warren, Sarah; Adjemian, Sandy; Agostinis, Patrizia; Martinez, Aitziber Buqué; Chan, Timothy A; Coukos, George; Demaria, Sandra; Deutsch, Eric; Draganov, Dobrin; Edelson, Richard L; et al.
Abstract : Cells succumbing to stress via regulated cell death (RCD) can initiate an adaptive immune response associated with immunological memory, provided they display sufficient antigenicity and adjuvanticity. Moreover, multiple intracellular and microenvironmental features determine the propensity of RCD to drive adaptive immunity. Here, we provide an updated operational definition of immunogenic cell death (ICD), discuss the key factors that dictate the ability of dying cells to drive an adaptive immune response, summarize experimental assays that are currently available for the assessment of ICD in vitro and in vivo, and formulate guidelines for their interpretation.